Valoración ambiental del cerro Putzalahua ubicado en la parroquia Belisario Quevedo, cantón Latacunga. Propuesta de conservación, 2022. - Cordones Araque, Kerly Galilea (2022)
The research project is based on the current state of Putzalahua hill in order to diagnose, evaluate and propose environmental conservation strategies through evaluation techniques and methods. It was specifically proposed through climatic conditions; current land use and surveys, it was evaluated through the Shannon index and the development of the environmental conservation proposal was proposed. The qualitative method helped to determine general information such as location, analysis of climatic conditions: precipitation, temperature, and relative humidity; current land use conditions: vegetation cover, texture, and forestry aptitude; on the other hand, the quantitative data helped to gather the survey information. The inductive method determined the total number of species, and with the calculation of the Shannon index, the biological diversity of the site was defined. The deductive method determined the environmental conservation proposal. It was determined that at present the climatic conditions of the site are altered due to the loss and deterioration of the vegetation cover and therefore the authenticity of its landscape. With Shannon's calculation, the diversity index of tree species is 1.0 and herbaceous and shrub species is 2.3, and the diversity of flora is 2.3, considering that the biological diversity in the study area is low. Strategies were developed for the conservation and environmental protection proposal. It is concluded that its current state is exploited and deteriorated due to anthropic intervention and recreational activities causing a low biological ecosystem. Therefore, a conservation and protection proposal was made.